Optimization of pH to Bacteriocin Production by Lactobacillus plantarum Against Methicillin-Resistant Staphylococcus aureus - Khumaira, Naila El; Suryani , Lilis (Universitas Muhammadiyah Yogyakarta, 2025)
Introduction: Methicillin-resistant Staphylococcus aureus (MRSA) is a bacterium that is resistant to beta-lactam antibiotics. MRSA is transmitted through skin/object contact and is often found in health care and the community. MRSA infection has a high mortality and morbidity rate because it causes sepsis, septic shock, respiratory failure, and amputation. Lactobacillus plantarum produces bacteriocin. The growth of both gram-positive and gram-negative bacteria can be inhibited by this bacteriocin. Purpose: To determine the effect of pH on the activity of bacteriocins produced by Lactobacillus plantarum against MRSA. Method: This research used quasi-experimental methods. L.plantarum was grown in liquid MRS media for 48 hours. Bacteriocin was obtained by centrifuging an MRS broth containing bacteria at a speed of 6000 rpm for 40 minutes. Using the Kirby Bauer method, the liquid formed was tested for its antibacterial effect against MRSA bacteria. Bacteriocins were treated with different pH, namely, 2, 4, 6, 8, and 10. The diameter of the inhibition zone formed during the testing process is measured in millimeters. Data were analyzed using the ANOVA method. Finding: The bacteriocin activity produced by Lactobacillus plantarum against MRSA shows an average diameter of the inhibition zone of 3 mm. The optimum broadest spectrum of antibacterial activity was shown in bacteriocins treated with pH 2. Conclusion: This study shows the results that pH does not affect the antibacterial activity of bacteriocins produced by L.plantarum against MRSA. Originality/Implication: The results of this study prove that various pH treatments do not affect the ability of the bacteriocin produced by L.plantarum to inhibit/kill MRSA.